Peran Self-Efficacy sebagai Variabel Mediasi antara Supervisi Klinik dan Keterampilan Praktik Kebidanan Mahasiswa - Ayu Ainun Khofifah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Midwifery practice skills are one of the main competencies that students must have to provide professional, safe, and quality midwifery services. However, the achievement of clinical practice competencies is not only influenced by the quality of clinic supervision, but also by student psychological factors, especially self-efficacy. This study aims to analyze the influence of clinical supervision on students' midwifery practice skills with self-efficacy as a mediating variable. The research uses a quantitative approach with an explanatory research design  and a cross-sectional design. A total of 250 midwifery students who had participated in clinical practice were selected as respondents using the proportionate random sampling technique. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that clinical supervision had a positive and significant effect on self-efficacy (β = 0.734; p < 0.001) and obstetric practice skills (β = 0.341; p < 0.001). In addition, self-efficacy also had a positive effect on midwifery practice skills (β = 0.523; p < 0.001) and was shown to partially mediate the relationship between clinical supervision and midwifery practice skills. These findings show that improving the quality of clinical supervision that is able to build student self-confidence is an effective strategy in improving the competence of midwifery practice. This research contributes to the development of a clinical learning model that integrates pedagogical and psychological aspects to produce midwifery graduates who are competent, professional, and ready to face the demands of health services.